Meta-analysis shows that mesenchymal stem cell therapy can be a possible treatment for diabetes - Umm E. Habiba; Umm E. Habiba; Umm E. Habiba; Nasar Khan; Nasar Khan; Nasar Khan; Nasar Khan; David Lawrence Greene; David Lawrence Greene; David Lawrence Greene; David Lawrence Greene; Khalil Ahmad; et al. (Frontiers in Endocrinology, 2024)
ObjectiveThis meta-analysis includes the systematic literature review and meta-analysis involving clinical trials to assess the efficacy and safety of mesenchymal stem cell (MSC) transplantation for treating T1DM and T2DM.MethodsWe searched PubMed, ScienceDirect, Web of Science, clinicaltrials.gov, and Cochrane Library for “published” research from their inception until November 2023. Two researchers independently reviewed the studies’ inclusion and exclusion criteria. Our meta-analysis included 13 studies on MSC treatment for diabetes.ResultsThe MSC-treated group had a significantly lower HbA1c at the last follow-up compared to the baseline (MD: 0.95, 95% CI: 0.33 to 1.57, P-value: 0.003< 0.05), their insulin requirement was significantly lower (MD: 0.19, 95% CI: 0.07 to 0.31, P-value: 0.002< 0.05), the level of FBG with MSC transplantation significantly dropped compared to baseline (MD: 1.78, 95% CI: -1.02 to 4.58, P-value: 0.212), the FPG level of the MSC-treated group was significantly lower (MD: -0.77, 95% CI: -2.36 to 0.81, P-value: 0.339 > 0.05), and the fasting C-peptide level of the MSC-treated group was slightly high (MD: -0.02, 95% CI: -0.07 to 0.02, P-value: 0.231 > 0.05).ConclusionThe transplantation of MSCs has been found to positively impact both types of diabetes mellitus without signs of apparent adverse effects.